2014
DOI: 10.5194/bgd-11-6555-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors controlling shell carbon isotopic composition of land snail <i>Acusta despecta sieboldiana</i> estimated from lab culturing experiment

Abstract: Abstract. The carbon isotopic composition (δ13C) of land snail shell carbonate derives from three potential sources: diet, atmospheric CO2, and ingested carbonate (limestone). However, their relative contributions remain unclear. Under various environmental conditions, we cultured one land snail species, Acusta despecta sieboldiana collected from Yokohama, Japan, and confirmed that all of these sources affect shell carbonate δ13C values. Herein, we consider the influences of metabolic rates and temperature on … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
(68 reference statements)
1
7
0
Order By: Relevance
“…In contrast, however, our regression line for Bradybaena shows an apparent deviation and has a higher intercept (Figure S6b); this is possibly attributed to the larger CIF at a lower temperature because our previous study exhibited that the calcification temperature of Bradybaena was 3 ~ 5 °C lower than that of Cathaica (Wang et al, ; Zhai et al, ). Similar changes in shell CIF with temperature were observed in a recent land snail culturing experiment (Zhang, Yamada, et al, ). Based on the newly obtained CIFs for the two genera determined here, the calculated δ 13 C of snail organic tissues is ‐28.29‰ to ‐24.74‰ for Bradybaena snails and ‐26.82‰ to ‐19.10‰ for Cathaica snails.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In contrast, however, our regression line for Bradybaena shows an apparent deviation and has a higher intercept (Figure S6b); this is possibly attributed to the larger CIF at a lower temperature because our previous study exhibited that the calcification temperature of Bradybaena was 3 ~ 5 °C lower than that of Cathaica (Wang et al, ; Zhai et al, ). Similar changes in shell CIF with temperature were observed in a recent land snail culturing experiment (Zhang, Yamada, et al, ). Based on the newly obtained CIFs for the two genera determined here, the calculated δ 13 C of snail organic tissues is ‐28.29‰ to ‐24.74‰ for Bradybaena snails and ‐26.82‰ to ‐19.10‰ for Cathaica snails.…”
Section: Discussionsupporting
confidence: 83%
“…Land snail culture experiments have revealed that plant dietary carbon accounts for almost 100% of shell carbon and that if the snail is fed an added CaCO 3 source, the ingested carbonate makes no contribution to δ 13 C shell values (Metref et al, ; Stott, ). However, the results of a more recent study showed that land snails ingested a considerable amount of carbonate (up to 26%) and that the corn‐fed (C 4 plants) groups ingested more carbonate than the cabbage‐fed (C 3 plant) groups had, which suggests the potential effect of a food preference on δ 13 C shell (Zhang, Yamada, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Where there is an obvious food preference among land snail species, for instance, as reported by Suzuki and Yamashita (1967), Hatziioannou et al (1994), Baldini et al (2007), Zhang et al (2014) Figure 4, Balakrishnan & Yapp, 2004), can vary by as much as 3&. Where there is an obvious food preference among land snail species, for instance, as reported by Suzuki and Yamashita (1967), Hatziioannou et al (1994), Baldini et al (2007), Zhang et al (2014) Figure 4, Balakrishnan & Yapp, 2004), can vary by as much as 3&.…”
Section: A Framework On the Sources And Controlling Factors Of Land Smentioning
confidence: 88%
“…As previously reported (Zhang et al, 2014), eight adult snails of Acusta despecta sieboldiana were collected in Suzukakedai, Yokohama, Japan and were cultured at room temperature (ca. 258C) from January 2012 and allowed to mate and lay eggs.…”
Section: Culturing Of Land Snailsmentioning
confidence: 99%
“…Four studies used laboratory-controlled experiments to examine stable carbon isotope systematics in snail diet, shell, and body tissue (Stott, 2002; Metref et al, 2003; Liu et al, 2007; Zhang et al, 2014), although none have investigated the oxygen isotope composition of land snails under laboratory conditions. The absence of laboratory-based oxygen isotope studies is likely attributable to the difficulty in quantitatively constraining the relatively high number of environmental variables affecting the snail oxygen isotope composition (Balakrishnan and Yapp, 2004).…”
Section: Introductionmentioning
confidence: 99%